2021
DOI: 10.3390/cells10113254
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 5′,8′-Cyclo-2′-Deoxypurines on the Base Excision Repair of Clustered DNA Lesions in Nuclear Extracts of the XPC Cell Line

Abstract: Clustered DNA lesions (CDL) containing 5′,8-cyclo-2′-deoxypurines (cdPus) are an example of extensive abnormalities occurring in the DNA helix and may impede cellular repair processes. The changes in the efficiency of nuclear base excision repair (BER) were investigated using (a) two cell lines, one of the normal skin fibroblasts as a reference (BJ) and the second from Xeroderma pigmentosum patients’ skin (XPC), and (b) synthetic oligonucleotides with single- and double-stranded CDL (containing 5′,8-cyclo-2′-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(27 citation statements)
references
References 54 publications
9
18
0
Order By: Relevance
“…2). This observation was in good agreement with our previous, recently published studies of complex CDL in which RcdA was more easily repaired than ScdA by nuclear and mitochondrial extracts from eukaryotic cells (Boguszewska et al, 2021a;Kaźmierczak-Barańska et al, 2021;Boguszewska et al, 2021b). RcdA bends the DNA double helix to a greater extent than ScdA; therefore, DNA repair enzymes are more likely to recognize and remove it from the plasmid sequence (Karwowski, 2013).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…2). This observation was in good agreement with our previous, recently published studies of complex CDL in which RcdA was more easily repaired than ScdA by nuclear and mitochondrial extracts from eukaryotic cells (Boguszewska et al, 2021a;Kaźmierczak-Barańska et al, 2021;Boguszewska et al, 2021b). RcdA bends the DNA double helix to a greater extent than ScdA; therefore, DNA repair enzymes are more likely to recognize and remove it from the plasmid sequence (Karwowski, 2013).…”
Section: Resultssupporting
confidence: 92%
“…The mutation frequency increased in the following order: RcdA/dU0<ScdA/dU0<RcdA/dU-1<ScdA/ dU-1<RcdA/dU+1<ScdA/dU+1. The fact that clusters containing dU+1 (for both diastereomers of cdA) have the highest mutagenic potential corresponded to previous studies in eukaryotic models (Pearson et al, 2004;Cunniffe et al, 2014;Karwowski, 2019;Boguszewska et al, 2021a;Kaźmierczak-Barańska et al, 2021;Boguszewska et al, 2021b;Karwowski et al, 2014). It was found that the most abundant mutation in the case of ScdA/dU+1 was dU:G deletion (30.8%).…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…For example, AP sites are usually cleaved before base damage when located 5 bp from each other, and the resulting SSB is repaired first [28]. Furthermore, studies have shown that the presence of cdA impacts the action of repair proteins and/or the DNA repair efficiency of the second lesion within the cluster [7,8,10,19,[29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%